Mechanical Properties and Anisotropy in PbWO4 Single Crystal - 王红 张志军 赵景泰 徐家跃 胡关钦 李培俊 (Chinese physics letters, 2010)
The mechanical properties of PbWO4 （PWO） crystals grown by the vertical Bridgman method are systematically investigated using the microindentation technique. In the present work, the Vickers microhardness Hν, fracture toughness Kc, yield strength σy and friability index Bi of PbWO4 crystals are measured. The Vickers microhardness Hν on the （100） wafer is about 140 MPa, which means that PWO is a little soft＇＇ scintillator. The anisotropy of mechanical properties is also investigated under a steady load of 0.5 kg. The （100） wafer of the crystal exhibits combined mechanical properties more excellent than those of （111） and （001） wafers, and the values of Kc, σy, and Bi are 0.538 MPa＆#12539;m1/2, 51.11 kg/mm2 and 284.96 νm-1/2, respectively.